2019
DOI: 10.1186/s12870-019-1901-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TaPPH-7A haplotypes and development of a molecular marker associated with important agronomic traits in common wheat

Abstract: Background Premature senescence of flag leaf severely affects wheat yield and quality. Chlorophyll (Chl) degradation is the most obvious symptom during leaf senescence and catalyzed by a series of enzymes. Pheophytin pheophorbide hydrolase (Pheophytinase, PPH) gene encodes a Chl degradation hydrolase. Results In this study, the coding, genomic and promoter sequences of wheat TaPPH-A gene were cloned. The corresponding lengths were 1467 bp, 447… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…The given Pakistani wheat germplasm had high frequencies of unfavorable allelic variations for TaMOC-7A and TaPARG-2A, suggesting the potential of favorable haplotype introgression through functional markers. Previously, selection pressure was observed on TaSnRK2.3-1A/B (Miao et al, 2017), TaSnRK2.9-5A (Ur Rehman et al, 2019), TaSAP-7B (Wang et al, 2018), TaMOC-7A , TaLTPs-1A , TaPARG-2A (Li B. et al, 2016), and TaPPH-7A (Wang et al, 2019) favorable allelic variations in Chinese wheat cultivars where the frequencies of favored haplotypes had gradually increased from the beginning of the last century. Both PIC and H e values were higher in tetraploid wheat as compared to Pakistani hexaploid wheat.…”
Section: Allelic Variation At Loci Influencing Grain Related Traitsmentioning
confidence: 97%
See 2 more Smart Citations
“…The given Pakistani wheat germplasm had high frequencies of unfavorable allelic variations for TaMOC-7A and TaPARG-2A, suggesting the potential of favorable haplotype introgression through functional markers. Previously, selection pressure was observed on TaSnRK2.3-1A/B (Miao et al, 2017), TaSnRK2.9-5A (Ur Rehman et al, 2019), TaSAP-7B (Wang et al, 2018), TaMOC-7A , TaLTPs-1A , TaPARG-2A (Li B. et al, 2016), and TaPPH-7A (Wang et al, 2019) favorable allelic variations in Chinese wheat cultivars where the frequencies of favored haplotypes had gradually increased from the beginning of the last century. Both PIC and H e values were higher in tetraploid wheat as compared to Pakistani hexaploid wheat.…”
Section: Allelic Variation At Loci Influencing Grain Related Traitsmentioning
confidence: 97%
“…TaSnRK2.3-1A/1B (Miao et al, 2017), TaSnRK2.9-5A (Ur Rehman et al, 2019), TaPARG-2A (Li B. et al, 2016), TaSAP-7B (Wang et al, 2018), TaPPH-7A (Wang et al, 2019), and TaMOC1-7A are associated with higher grain yield under water stress conditions. TaSnRK2.8-5A associated with higher seedling biomass under normal conditions and water-soluble carbohydrates under limited irrigation conditions (Zhang et al, 2013), TaLTPs-1A associated with ideal plant height under drought conditions , and TaDreb-B1 (Wei et al, 2009) and 1-feh w3 are also reported as drought toleranceconferring genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors like DREB control the expression of several functional genes responsible for plant tolerance to drought, and have been proposed for use in plant improvement for drought tolerance [ 33 ]. Similarly, TaTEF-7A is transcript elongation factor gene responsible for grain number per spike [ 34 ], thousand grain weight and chlorophyll content at grain-filling stage under drought stress [ 35 ]. The gene TaPRR73 was found to be regulation of flowering date and can be used in breeding to develop cultivars adaptable for different geographical areas [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors like DREB known to control the expression of several functional genes responsible for plant tolerance to drought, high-salt and cold stress and have been propose to use in plant improvement for stress tolerance (28). Similarly, TaTEF-7A is transcript elongation factor gene responsible for number per spike (29) and thousand grain weight under (30). The gene TaPRR73 was found to be regulation of flowering date and can be used in breeding to develop cultivars adaptable for different geographical areas (31).…”
Section: Introductionmentioning
confidence: 99%